Word-of-mouth innovation: A product development shortcut for organic skin care entrepreneurs in Thailand? - Vittayavarakorn, Narit; Sornsaruht, Puris (My University, 2024)
This study explores the impact of perceived quality, brand attitude, consumer satisfaction, and the marketing mix on word-of-mouth innovation (WOMI) in the organic skincare industry in Thailand. Systematic random sampling was used in 2023 to select 453 organic skincare users whose questionnaire was expert-validated and tested. Investigating these interconnected factors, the research contributes to consumer behavior and innovation theories. It reveals crucial links, notably between brand attitude and perceived quality, expanding theoretical frameworks. Beyond theoretical advancements, the study provides actionable insights for entrepreneurs, marketers, and policymakers. Recognizing the pivotal role of consumer reviews in driving WOMI, industry stakeholders can enhance product quality, tailor marketing strategies, and foster innovation. Bridging theory and practice, this research empowers stakeholders to make informed decisions, adapt strategies, and contribute to the growth of the organic skincare sector. In conclusion, the study enhances theoretical understanding while offering practical implications, fostering a symbiotic relationship between academic knowledge and industry advancements.
Keywords: brand attitude; consumer satisfaction; marketing mix; perceived quality; Thailand